PENGARUH STRUCTURE OWNERSHIP DAN KARAKTERISTIK AUDITOR TERHADAP TAX AVOIDANCE PADA PERUSAHAAN DALAM IDXV30 DI BURSA EFEK INDONESIA - Rahadian Cahyadi; Fadliah Nasaruddin; Darwis Lannai (INVOICE : JURNAL ILMU AKUNTANSI, 2020)
This study aims to determine the effect of Structure Onwership and Auditor Characteristics on Tax Avoidance in IDXV30 on the Indonesia Stock Exchange. This study uses a quantitative method with the acquisition and secondary data collection. The companies that became the sample of this study were 30 companies that applied accounting conservatism. The number of samples that could be analyzed were 30 samples, thus the number of samples over three years was 90 samples (30x3). The results of the X1 Variable Test (Structure Ownership) gave a parameter coefficient (t-count) of 1,809 with a significance level of 0.07 (0.10). This means that H1 is accepted (Hair, 2017) so it can be said that Structure Ownership has a positive and significant effect on Tax Avoidance Variable X2 (Characteristics of Auditors) giving a parameter coefficient value of 0.02 (0.05). This means that H1 is accepted so that it can be said that the auditor's characteristics have a significant and significant effect on tax avoidance because the level of significance possessed by the auditor's variable characteristics 0.05 (0.02 0.05) and tcount 1.668 (2,347 1,668).